2009
DOI: 10.4028/www.scientific.net/msf.620-622.181
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on Solar Heat Reflective Coatings to Reduce Asphalt Concrete Temperature

Abstract: As the development of civil construction, the heat island effect in large cities of China has gradually become a social issue. Pavements, especially asphalt pavements, are considered to be one of the main causes of the heat island effect as they cover wide area of cities. In some regions, the surface of asphalt pavements can even be heated up to more than 70°C by solar irradiation in summer times due to the excellent heat-absorbing property of asphalt concrete. In this paper, a solar heat reflective coating on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The functional filler comprises TiO 2 and SiO 2 . High reflectivity guarantees the cooling effect of heat-reflective coatings; the higher the coating reflectivity, the better its cooling effect [21,39,40]. Therefore, in this study, the functional filler content was optimized based on the resulting cooling effect.…”
Section: Reflective Filler Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional filler comprises TiO 2 and SiO 2 . High reflectivity guarantees the cooling effect of heat-reflective coatings; the higher the coating reflectivity, the better its cooling effect [21,39,40]. Therefore, in this study, the functional filler content was optimized based on the resulting cooling effect.…”
Section: Reflective Filler Selectionmentioning
confidence: 99%
“…Cao et al compared the internal temperature of asphalt and heat-reflective pavements; At 2.5 cm depth, the temperature of the traditional pavement reached 62.7 • C, while that of the heat-reflective one was reduced by 9 • C [12]. Outdoor tests and experiments on test sections have also been conducted to further confirm the cooling effect of heat-reflective coatings [7,10,20,21]. Furthermore, Jiang et al reported that heat-reflective pavements have better stability at high temperatures [17,22,23].…”
Section: Introductionmentioning
confidence: 99%